Does oyster mushroom (Pleurotus sajorcaju) powder addition improve nutrient composition, sensory acceptability, and glycaemic index (GI) of flatbread (Tortilla)? - Wan Ishak, Wan Rosli Wan; Wan Amir Nizam WAN AHMAD; Nordiana ABU BAKAR (Kuwait Journal of Science, 2021)
Regular consumption of dietary fibre (DF) has been proven to reduce the risk of non-communicable diseases which lead to the rising demand for DF-enriched products. The study aims to investigate the effect of Pleurotus sajorcaju powder (PSP) incorporation on the nutrient composition, sensorial acceptability and glycaemic index (GI) of the developed tortilla. Four tortilla formulations with different levels of PSP (0%, 5%, 10%, and 15%) to replace wheat flour partially were prepared. The concentration of protein in control tortilla was 8.26% and increased to 9.31, 9.72 and 10.60% when incorporated with 5, 10 and 15% PSP, respectively. Both the 10% and 15% PSP tortilla (12.00% and 13.62%) were found to be significantly higher than the control tortilla in total DF. The β-glucan content was the highest in the tortilla with 15% PSP added (1.21%). In sensory evaluation, the tortilla fortified up to 15% PSP was apparently well accepted by the sensory panelists. Control tortilla had an intermediate GI value (58) while 15% PSP tortilla had a low GI value (53). In summary, an addition of up to 15% PSP in the tortilla formulation was found to increase nutritional values, improving the sensorial attributes and reducing GI value.